Workshop Asesmen dalam Pembelajaran Berdiferensiasi pada Kurikulum Merdeka - Juidah, Imas; Saroni, Saroni (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2025)
Differentiated learning is an approach that allows teachers to adapt learning to students' needs, interests and level of readiness. This workshop aims to increase teachers' understanding regarding assessment in differentiated learning in the Independent Curriculum. The method used in this workshop is interactive training involving group discussions, material presentations, and assessment simulations. Data was collected through participant observation, participant satisfaction questionnaires, and in-depth interviews with several teachers. Data analysis was carried out descriptively by examining the effectiveness of the workshop based on participant involvement and their understanding of the material. The results of the workshop showed that 90% of participants were actively involved in the activities and 94% stated that the workshop was very relevant to their needs. These findings indicate that differentiated assessment workshops can increase teacher competence in implementing assessments that are flexible and appropriate to the needs of students in the classroom.